Authors' response: letter to the editor "Comparison of lung clearance index determined by washout of N2 and SF6 in infants and preschool children with cystic fibrosis" - Stahl, Mirjam; Joachim, Cornelia; Wielpütz, Mark Oliver; Mall, Marcus A. (Journal of cystic fibrosis, 2019)
We thank Alex Horsley and colleagues for their interest in our study comparing lung - clearance index (LCI) derived from nitrogen (N2)- and sulfur hexafluoride (SF6)- multiple - breath washout (MBW), including an analysis of the relationship of both LCI values - with proton magnetic resonance imaging (MRI) for assessment of lung disease in preschool - children with cystic fibrosis (CF) [1]. We agree with the authors that further research - on MBW methodology is needed to clarify the reason underlying the difference between - LCI values obtained by washout of N2 vs.
Gesehen am 27.04.2020